Performance of thermoacoustic tiles in sheds on a reduced scale for layering chickens - Mollo Neto, Mario; Moreira Da Silva, Brayam; Sartori , Diogo de Lucca (Revista Brasileira de Engenharia de Biossistemas, 2022)
Climate change significantly affects the production and welfare of laying hens. In this research, the thermal performance of three different roofs for sheds composed of ceramic, fiber-cement, and thermo-acoustic tiles was analyzed in order to ascertain the performance and thermal comfort levels of the different roofs, observing the thermal comfort conditions inside the environment of the buildings. sheds. The indoor environment was monitored by recording equipment such as data loggers and sensors, which collected temperature and relative humidity data from February to March 2020. The data from the indoor environment of the facilities were used to calculate the comfort indexes for chickens laying hens. With the results, it was observed that the ceramic tile had more adequate BGHI and ET performance than the others, and the thermoacoustic tile presented a lower performance for the THI compared to the others. All tiles had a similar RTL result, with a minimal difference between them, with a significant difference occurring in two periods for thermoacoustic tiles. Thus, it is demonstrated that the ceramic tile had the best thermal performance.